METHODOLOGICAL FOUNDATIONS OF PROFESSIONAL INTEREST FUTURE MUSIC TEACHERS - Bilous., O. O. (Continuing Professional Education: Theory and Practice, 2023)
part of complex system of educational conditions in teacher training colleges. It is laid objective conditions for the development of interest of future professional teachers to the content of the training material musical-theoretical disciplines. Also it is revealed cycle substantive competence music-theoretical subjects. The article defines the concept of «professional interest of future music teachers» analyzes the methodological approaches to the development of this phenomenon. Particular attention is given to student-centered, competence, axiological approach, reflecting the humanistic orientation of education of future music teachers. It appears that for more effectiveness of implementation of these approaches should be made a special organization of educational process in pedagogical colleges. The main emphasis is on necessary of creative direction of integrated training of future music teacher. The motives of choosing the profession of music teacher are investigated, pedagogical value, which should be formed from representatives of the profession are defined.